Perlindungan Hukum terhadap Pekerja dalam Proses Penyelesaian Sengketa di Pengadilan Hubungan Industrial - Meiske Abdullah; Roy Marthen Moonti; Ibrahim Ahmad (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
The government needs to strengthen the industrial relations dispute resolution system so that it is more accessible to workers. This strengthening can be carried out through the equitable distribution of Industrial Relations Courts, simplification of litigation procedures, improvement of legal aid services, and assistance for workers who lack an understanding of labor law. The use of e-court also needs to be optimized, but it must be accompanied by digital literacy and supporting facilities so that it does not create new obstacles. In addition, a special enforcement mechanism should be established in industrial relations cases so that Industrial Relations Court decisions can be implemented immediately and workers’ rights are not delayed. Judges, mediators, labor inspectors, and labor unions also need to improve their capacity and commitment to substantive justice. Employers are expected to comply with court decisions voluntarily and prioritize deliberative settlement from the initial stage. Through these reforms, the Industrial Relations Court will not merely serve as a formal forum, but will truly function as a means of legal protection that is fast, affordable, certain, and just for workers.